HOW EXACTLY DO UPLAND FARMERS FIGHT POVERTY?: AN ETHNOGRAPHY ON UPLAND FARMERS’ IN AN UPLAND VISAYAN FARMING VILLAGE USE OF DIVERSIFICATION ACTIVITIES AS ANTI-POVERTY TOOL - Bernados, Simeon C; Villarin, Imelda J (Journal of Agriculture and Technology Management; Vol 25 No 1 (2022): Vol 25 No 1 (2022): Journal of Agriculture and Technology Management (JATM) Volume 25 January - June 2022 Issue, 2022)
The elimination of poverty in all forms is a challenge that the United Nations must address (SDG 1). Poverty is a complex phenomenon and income poverty, especially in rural areas, is a paramount concern that needs to be addressed. A 12-month ethnographic study was conducted to investigate the contribution of upland farmers’ diversification activities (DAs) to meet financial requirements for farm operations and household subsistence. Fieldwork was conducted during the academic breaks. This study was guided by the following questions: (a) How do DAs reduce poverty? (b) What are the different DAs undertaken by the upland farmers? The results showed that upland farmers had a relatively low time input (95.57 h) in all phases of the agricultural cycle compared to workers in the industrial sector. Furthermore, upland farmers undertook both livelihood diversification (LD) and crop diversification (CD) to meet farm requirements and household subsistence. These activities were timed during off-farm or slack periods. It is recommended that provisions for farm-to- market roads and extension services are provided to rural farmers. Towards this end, governments, through their line agencies, shall come up with policies and programs in support of farmers’ economic endeavors such as training and extension and technical services to achieve the goal of a poverty-free community.